The mediating role of resilience and interaction anxiousness in the effects of physical activity on mobile phone addiction among Chinese college students - Wu, Jinlong; Xiao, Wen; Liu, Bowen; Yu, Jingxuan; Zheng, Kangyong; Shi, Qiuqiong; Ren, Zhanbing (Frontiers in Psychiatry, 2024)
Background: Recent studies have shown that regular physical activity (PA) can positively influence mobile phone addiction (MPA) behaviors in college students.However, it remains unknown whether this effect is mediated by other factors.Evidence suggests that resilience and interaction anxiousness may be candidate mediators that partly explain the positive effect of PA on MPA. This study aims to explore the impact of PA on MPA through a mediation model, and the role of resilience and interaction anxiousness in this relationship.The participants were 590 college students (272 males; mean age = 19.67) who completed a psychosocial battery, including the international physical activity questionnaire-short form (IPAQ-SF), the connor -davidson resilience scale (CD-RISC), the interaction anxiousness scale (IAS), and the mobile phone addiction index (MPAI). Correlations of variables were computed using Pearson's test.Mediation models were tested using SPSSS PROCESS macro with the regression bootstrapping method.Results: PA were negatively associated with MPA behavior (r=-.21, p ＜ 0.01).Resilience and interaction anxiousness moderated the relationship between PA and MPA. More importantly, PA could also influence MPA through the chain-mediating effects of resilience and interaction anxiousness.It is essential to improve resilience and reduce interaction anxiousness to reduce MPA problems through regular engagement in PA among college students.